Assessment of Psychological Wellbeing Among Elderly Residents at Nursing Homes in Middle Euphrates - Bashaer Mohsen Ali; Ali Kareem Al-Juboori (Institute of Medico-legal Publications Pvt Ltd, 2021)
As people get older, may show shifts in the main sources that contribute to their well-being, in responseto the changing circumstances and abilities inherent in aging. The relocation to care homes considered asstressful event for the elderly people. A descriptive study is carried throughout the present study in orderto achieve the early stated objectives. The selection of the sample through a non - probability purposivesample consist of 60 elderly persons that are selected from the total population of elderly residents at nursinghomes. The data is collected by means of Ryff scales of psychological well-being (shorten version) . Thedata is collected by using structured interview technique with the elderly residents in nursing homes. Theanalysis indicates that the highest percentage of the elderly’s group have moderate level of psychologicalwellbeing (mean of score=3.29) (81.67%). The level of psychological well-being is affected by their gender.The study recommends to focus on managing the problems existing among the elderly and monitoring theirpsychological state.